'It was clear from the start that [SDS] was about a cost cutting agenda.' Exploring disabled people's early experiences of the introduction of Self-Directed Support in Scotland. Issue 9 (21st October 2018) - Manji, Kainde
Abstract: The adoption of personalisation represents a global paradigm shift in the organisation of social care. However, such approaches have been criticised for failing to bring about transformative change. The passage of the Self-Directed Support (Scotland) Act (2013) was intended to bring about a significant change in the organisation of social care in Scotland, giving increased choice and control to new user groups. The implementation of the policy at a time of significant financial constraint for local government has cast doubt on this potential. This paper presents findings reflecting disabled peoples' lived experience of this change during the early stages of implementation. Drawing on one-to-one qualitative interviews with disabled people living across the central belt of Scotland, this early snapshot suggests that the policy had not significantly increased choice and control for service users, and that austerity was leading to an erosion of gains made by existing Direct Payments users.